2021
DOI: 10.1177/1540415320985590
|View full text |Cite
|
Sign up to set email alerts
|

Provider Perspectives on Latino Immigrants’ Access to Resources for Syndemic Health Issues

Abstract: Introduction: Latino immigrants to the United States experience disproportionate impacts from the syndemic formed by substance abuse, violence victimization, HIV/AIDS, and mental health (SAVAME). This study characterizes resource access for Latino immigrants living in Philadelphia, as perceived by staff at Latino-serving organizations. Methods: An online cross-sectional survey of staff at key Latino-serving Philadelphia organizations assessed access to their organization and citywide access to each type of ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
5
5
0
Order By: Relevance
“…The limited funding creates important challenges for Latino-serving organizations to hire, train and retain bilingual and bicultural staff to support Spanish-language, culturally tailored, trauma-informed substance use and mental health services for immigrant communities. The results resonate with and expand the LINKS data, which also showed lower availability scores for mental health and substance use services in Philadelphia compared to HIV/AIDS and domestic violence (Giordano et al, 2021).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The limited funding creates important challenges for Latino-serving organizations to hire, train and retain bilingual and bicultural staff to support Spanish-language, culturally tailored, trauma-informed substance use and mental health services for immigrant communities. The results resonate with and expand the LINKS data, which also showed lower availability scores for mental health and substance use services in Philadelphia compared to HIV/AIDS and domestic violence (Giordano et al, 2021).…”
Section: Discussionsupporting
confidence: 74%
“…These ndings are consistent with previous literature describing the SAVAME syndemic in Latino populations (González-Guarda et al, 2011;Martinez, 2020) in the U.S. and earlier calls for a syndemic approach in the prevention and treatment of these interrelated epidemics (Rosa Maria Gonzalez-Guarda, 2009). The providers's responses were also in line with ndings from the earlier LINKS survey, which showed that only 20% of the Latino-serving providers surveyed considered integration of SAVAME services in the city was good and 19% reported that their organizations routinely screened their clients for all four SAVAME factors (Giordano et al, 2021). Together, these results highlight a missed opportunity to identify and address concurrent SAVAME needs experienced by Latino immigrants presenting at Latino-serving organizations.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Provision of services within local communities, as well as offering extended hours, are also organizational approaches found to improve access to care (139)(140)(141). In addition to helping services to be available from a logistical standpoint, organizations can foster an environment in which providers have opportunities to learn about cultural responsiveness, sources of resilience, and best practices with Latino communities (111,125,129,140). Within this context, organizations might provide formal trainings, either in person or online, to increase knowledge, cultural competence, and cultural humility related to serving Latino communities.…”
Section: Discussionmentioning
confidence: 99%
“…-Mexicans, Central Americans, South Americans) or U.S. citizens from Puerto Rico living in the city. The survey (N = 31, 72% response rate) showed that syndemic services for Latino immigrants in Philadelphia ranked low in terms of availability, accessibility, and adequacy [21]. These three factors are considered important dimensions within the general concept of access to services [22].…”
Section: Introductionmentioning
confidence: 99%